EBSD orientation analysis based on experimental Kikuchi reference patterns. (15th April 2020) - Winkelmann, Aimo; Cios, Grzegorz; Tokarski, Tomasz; Nolze, Gert; Hielscher, Ralf; Kozieł, Tomasz
Abstract: Orientation determination does not necessarily require complete knowledge of the local atomic arrangement in a crystalline phase. We present a method for microstructural phase discrimination and orientation analysis of phases for which there is only limited crystallographic information available. In this method, experimental Kikuchi diffraction patterns are utilized to generate a self-consistent master reference for use in the technique of Electron Backscatter Diffraction (EBSD). The experimentally derived master data serves as an application-specific reference in EBSD pattern matching approaches. As application examples, we map the locally varying orientations in samples of icosahedral quasicrystals observed in a Ti40Zr40Ni20 alloy, and we analyse AlNiCo decagonal quasicrystals. Graphical abstract: